KERAGAAN USAHATANI TANAMAN HORTIKULTURA PADA KAWASAN AGROPOLITAN KECAMATAN BELIK KABUPATEN PEMALANG - - - Watemin; Rahma Hayati Putri (Surya Agritama : Jurnal Ilmu Pertanian dan Peternakan, 2015)
This research aims to know the variability of horticultural crop in agropolitan region Belik Sub District. This location was selected because Belik Sub District is one of the center of Waliksarimadu Agropolitan Region in Pemalang Regency.  The research was conducted by using survey method.  Sixty farmers sampling were taken as Simple Random Sampling.  It also provided quantitative analysis to determine the variability of horticultural crop.  Result showed that 38.33% of farmers cultivate vegetables, 33.33 % of farmers cultivate fruits, and 18.33 % of farmers cultivate medicine (spice). Keywords : Variability, Horticultural, Agropolitan